WHAT IS NORDIC WALKING, FINNISH WALKING, NORDIC WALKING WITH STICKS, SCANDINAVIAN WALKING? (Scientific journal of the Fergana State University, 2024)
This article contains general information about healthy Nordic walking, as well as the importance of walking in the health and strengthening of the population, its positive effect on the human body, the legal rules for conducting exercises, as well as the difference between Nordic walking and walking. walks and other sports.